Postmemory / Posthuman: Conversation with an AI about Bruno Bresani’s recent work (REVISTA NODO, 2025)
Asked by Bruno Bresani to publish an article in nodo magazine, I decided to try my hand at working with a chatbot to simulate a conversation that would lead to the article. What I didn't tell the chatbot was that this previous conversation would actually be the article.
Keywords: Art; Chatbot; Creativity; Artificial intelligence; Posthuman; Postmemory